The Endeavour of Indonesian Female Migrant Workers in Taiwan in Building Family Resilience - Gusman, Yuherina (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Abstrak Migrasi tenaga kerja internasional menyebabkan meningkatnya jumlah keluarga transnasional di Indonesia. Perbedaan geografis dan jangka waktu bermigrasi yang lama membuat keluarga transnasional terlibat dalam berbagai permasalahan dan tekanan psikologis khususnya pada anak-anak yang ditinggalkan. Tulisan ini bertujuan untuk mengkaji secara mendalam bagaimana upaya pekerja migran Indonesia di Taiwan dalam membangun dan mempertahankan ketahanan keluarga dalam kondisi yang tidak ideal tersebut. Selain itu tulisan ini juga menganalisa lebih dalam bagaimana remitansi membantu terciptanya ketahanan keluarga migran. Metode kualitatif digunakan dalam penelitian ini, data primer didapatkan dengan wawancara mendalam terhadap 10 pekerja migran perempuan Indonesia di Taiwan, 10 anak pekerja migran dan 10 pengasuh mereka di Indramayu, Jawa Barat. Metode snowball sampling digunakan untuk mendapatkan informan di Taiwan dan melalui purposive sampling untuk mengumpulkan informan di Indramayu. Penelitian ini menemukan bahwa upaya yang dilakukan dalam membangun ketahanan keluarga migran belum maksimal. Ketahanan ekonomi yang diperkirakan akan tinggi pada pekerja migran ternyata tidak tergambarkan pada penelitian ini sebagai salah satu indikator ketahanan keluarga migran. Lamanya masa migrasi di Taiwan tidak menjamin kuatnya ketahanan ekonomi keluarga migran. Dimensi lain seperti ketahanan psikologis, sosial, dan spiritual juga kurang kokoh sehingga menimbulkan dampak negatif bagi keluarga dan anak-anak yang ditinggalkan. Kata kunci: ketahanan keluarga, keluarga migran, keluarga transnasional, pekerja migran Indonesia Abstract International labor migration has led to a rise in transnational families in Indonesia. Transnational families face numerous challenges and psychological stress, particularly for left-behind children, owing to geographical separation and extended periods of migration. This study aimed to analyze the endeavors of Indonesian migrant workers in Taiwan to establish and sustain family resilience under unfavorable circumstances. In addition, this study aims to further examine how remittances foster resilience among migrant families. The research used qualitative methodologies by conducting in-depth interviews with 10 Indonesian female migrant workers in Taiwan, 10 left-behind children in Indonesia, and 10 caregivers as primary data. The snowball sampling technique was used to recruit participants in Taiwan, and purposive sampling was used for participants in Indonesia. This study determined that the efforts taken to enhance the resilience of migrant families have not been optimal. The economic resilience expected to be high among migrant workers is apparently not reflected in this study as an indicator of the resilience of migrant families. The duration of the migration period in Taiwan does not guarantee the solid economic resilience of migrant families. Additionally, the lack of robustness in other sectors, such as psychological, social, and spiritual resilience, leads to adverse consequences for families and children left behind. Keywords: family resilience, migrant family, transnational families, Indonesian migrant workers